The Determination of Psychological Safety, Resilience, and Transformational Leadership on Employee Performance Travel Company - Bekti Setiadi (International Journal of Psychology and Health Science, 2023)
The Influence of Psychological Safety, Resilience, and Transformational Leadership on Employee Performance is a literature study article within the scope of the field of human resource management. This article aims to build a hypothesis of influence between variables that will be used in further research. Research objects in online libraries, Research Gate, Elsevier, Google Scholar, Mendeley, and other academic online media. The research library method comes from e-books and open-access e-journals. The results of this article: 1) Psychological Safety influences Employee Performance; 2) Resilience influences Employee Performance; 3) Transformational Leadership influences Employee Performance.